A Retrospective Study of Pap Smears at A Tertiary Care Hospital - Jyoti Sapre; Nilam Patel; Kirti Vyas (International Journal of Pharma and Bio Sciences, 2023)
Cervical cancer is India’s 3rd most common cause of malignancy and the second leading cause of morbidity and mortality. A Pap smear is a practical and convenient test to diagnose premalignant and malignant lesions of the cervix at an early stage. This study aimed to evaluate the cytological features of cervical smears taken at a tertiary care hospital to detect precancerous and cancerous lesions. These lesions have a long latent period until they reach the full-blown stage of malignancy. It is important that these lesions must be diagnosed early. This was a retrospective study on 1000 Pap smears studied in the pathology department at a tertiary care hospital from 1st April 2018 to 30th April 2021. The samples were taken from women between the ages of 20 and 80 years coming to our hospital’s gynecological Outpatient department (OPD). In our study, the maximum number of women was between the ages of 31 to 40 years (35.1%), followed by 41 to 50 (32.2%). Abnormal findings were reported in 38 cases (3.8%) - atypical squamous cells of undetermined significance (ASCUS) were reported in 21 patients (2.1%), Low-grade Squamous Intraepithelial Lesion (LSIL) in 6 cases (0.6%), High-grade Squamous Intraepithelial Lesion (HSIL) in 8 cases (0.8), Atypical Glandular Cells of Uncertain Significance (AGUS) in 1 patient (0.1%) and Adenocarcinoma cervix in 2 cases (0.2%). Unsatisfactory smears were reported in 92 cases (9.2%), while the rest of the pap smears were reported normal, which included Inflammatory lesions (74.2%), Bacterial vaginosis (19.7%), Candida infection (4.25%) and trichomonas vaginalis (1.72%). A Pap smear test is an inexpensive and convenient procedure that can detect premalignant and malignant lesions of the cervix early and should be used as a screening test at regular intervals in women of vulnerable age groups.